Use of antibiotics in paediatric long-term care facilities. Issue 2 (June 2018) - Murray, M.T.; Johnson, C.L.; Cohen, B.; Jackson, O.; Jones, L.K.; Saiman, L.; Larson, E.L.; Neu, N.
Summary: Background: Adult long-term care (LTC) facilities have high rates of antibiotic use, raising concerns about antimicrobial resistance. Few studies have examined antibiotic use in paediatric LTC facilities. Aim: To describe antibiotic use in three paediatric LTC facilities and to describe the factors associated with use. Methods: A retrospective cohort study was conducted from September 2012 to December 2015 in three paediatric LTC facilities. Medical records were reviewed for demographics, healthcare-associated infections (HAIs), antimicrobial use and diagnostic testing. Logistic regression was used to identify predictors for antibiotic use. The association between susceptibility testing results and appropriate antibiotic coverage was determined using Chi-squared test. Findings: Fifty-eight percent (413/717) of residents had at least one HAI, and 79% (325/413) of these residents were treated with at least one antibiotic course, totalling 2.75 antibiotic courses per 1000 resident-days. Length of enrolment greater than one year, having a neurological disorder, having a tracheostomy, and being hospitalized at least once during the study period were significantly associated with receiving antibiotics when controlling for facility (all P < 0.001). Diagnostic testing was performed for 40% of antibiotic-treated HAIs. Eighty-six percent of antibiotic courses for identified bacterial pathogens (201/233) provided appropriate coverage. Access to susceptibility testing was not associated with appropriate antibiotic choice ( P = 0.26). Conclusion: Use of antibiotics in paediatric LTC facilities is widespread. There is further need to assess antibiotic use in paediatric LTC facilities. Evaluation of the adverse outcomes associated with inappropriate antibiotic use, including the prevalence of resistant organisms in paediatric LTC facilities, is critical.